Kinetic proofreading can enhance specificity in a non-enzymatic DNA strand displacement network - Mukherjee,R; Sengar,A; Cabello,Garcia J; Ouldridge,T (Journal of the American Chemical Society, 2024)
Kinetic proofreading is used throughout natural systems to enhance the specificity of molecular recognition. At its most basic level, kinetic proofreading uses a supply of chemical fuel to drive a recognition interaction out of equilibrium, allowing a single free-energy difference between correct and incorrect targets to be exploited two or more times. Despite its importance in biology, there has been little effort to incorporate kinetic proofreading into synthetic systems in which molecular recognition is important, such as nucleic acid nanotechnology. In this article, we introduce a DNA strand displacement-based kinetic proofreading motif, showing that the consumption of a DNA-based fuel can be used to enhance molecular recognition during a templated dimeri zation reaction. We then show that kinetic proofreading can enhance the specificity with which a probe discriminates single nucleo tide mutations, both in terms of the initial rate with which the probe reacts and the long-time behaviour.